2018
DOI: 10.1002/tl.20318
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Master Teachers: German University Students’ Perceptions of High‐Quality Instruction

Abstract: To appreciate the value that German students place on specific qualities and behaviors of faculty whom they consider master teachers, it is beneficial to understand the structure of the educational system in Germany. The traditional model of education in Germany is based on a three-tiered academic system. Children begin elementary school at approximately 6 years old and complete 4 years of schooling, where they are then recommended by their teacher to enter one of three educational tracks based on their academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The second research question, which is complementary to the first, explored the categories' prevalence. Prior scholarship indicated that learners' perceptions of teachers are primarily mediated through relationship-oriented and affective dimensions, such as a teacher's approachability, honesty, trust, and respect toward students (Brinkworth et al, 2009;Henry & Thorsen, 2018;Zayac & Lenhard, 2018). Supporting previous studies, the most common categories featured affective dimensions.…”
Section: Learners' Knowledge Of Stereotypes About Teachersmentioning
confidence: 55%
“…The second research question, which is complementary to the first, explored the categories' prevalence. Prior scholarship indicated that learners' perceptions of teachers are primarily mediated through relationship-oriented and affective dimensions, such as a teacher's approachability, honesty, trust, and respect toward students (Brinkworth et al, 2009;Henry & Thorsen, 2018;Zayac & Lenhard, 2018). Supporting previous studies, the most common categories featured affective dimensions.…”
Section: Learners' Knowledge Of Stereotypes About Teachersmentioning
confidence: 55%
“…In another study, adolescents describe the teachers who are extroverted as ''liked'' teachers (Eryılmaz, 2014). Positive teacher characteristics are included under concepts such as effective (Isenberg et al, 2016;Külekçi, 2018) and master (Zayac & Lenhard, 2018). In the positive teaching model based on positive psychology proposed by Eryılmaz and Bek (2018), these characteristics are stated as having extroverted personality traits, experiencing flow during the lesson, telling the subject by embodying it, including the student in the lesson and establishing positive relationships with the student.…”
Section: Introductionmentioning
confidence: 99%